Numerical Assessment of Reinforced Concrete Beams Strengthened with CFRP Sheets under Impact Loading (Fracture and Structural Integrity, 2021)
This paper investigates numerically the behavior of Reinforced Concrete (RC) beams, strengthened using Carbon Fiber Reinforced Polymers (CFRP) sheets, subjected to impact loading. Three-dimensional finite element analysis was performed and its results were verified against experimental ones available in the literature showing good agreement. Then, a comprehensive parametric study was performed to investigate the effect of studied parameters on the strengthened RC beams. The main studied parameters were type and size of reinforcing bars, geometric characteristics of externally bonded CFRP sheets (width, length, and thickness), impact velocity, and the position of the impactor with respect to the beam. Results showed that the use of externally bonded CFRP sheets enhanced the beam capacity and failure mode, and reduced the mid-span deflection. Moreover, a reduction in the mid-span deflection was observed due to the use of CFRP bars as internal reinforcement. On the other hand, the deflection was increased due to the increase of the impact velocity, and the change of the impact load position.
Keywords: Concrete; RC Beams; Finite Element; Carbon Fiber Reinforced Polymers; Impact